Watermark based recovery of tampered documents - Makur, Anamitra (2013)
In this work recovery of text documents is addressed. Text documents are watermarked using pixel flipping based watermarking and self-embedding for not only authentication but eventual recovery in presence of tampering. A scheme is proposed that recovers against all possible editing attacks such as substitution, insertion and deletion of characters. Algorithms for tamper detection and recovery are suggested and their functioning explained with detailed examples.